Species delimitation in the genus Greenwayodendron based on morphological and genetic markers reveals new species - (:unkn) unknown (My University, 2019)
Combining genetic and morphological markers is a powerful approach for species delimitation, much needed in tropical species complexes. Greenwayodendron (Annonaceae) is a widespread genus of trees distributed from West to East African rainforests. Two species and four infra-specific taxa are currently recognized. However, preliminary genetic studies and morphological observations suggested the occurrence of additional species, undescribed to date. We tested species delimitation within Greenwayodendron by combining morphological and population genetics data. First, a visual inspection of about a thousand specimens suggested the existence of seven morphogroups: four of them occur in Central Africa and overlap in Gabon while three others are allopatric, occurring respectively in West Africa, East Africa, and the islands of São Tomé and Príncipe. Their morphological differentiation was confirmed by analysis of 27 morphological characters coded from 233 herbarium specimens. Second, after genotyping 800 samples at eight nuclear microsatellites, Bayesian clustering analyses (STRUCTURE) identified four genetic clusters corresponding to the well-sampled morphogroups but failed to separate the three remaining morphogroups represented by few samples. However, we show that this is an inherent limit of the STRUCTURE algorithm, whereas factorial correspondence analysis (FCA) and pairwise FST and RST measures confirmed the genetic differentiation of all morphogroups. We considered that a clear genetic differentiation occurring between sympatric populations advocates for recognizing distinct species following the biological species concept. Our analyses highlight that the current taxonomic treatment of Greenwayodendron underestimates the total number of species. We identified two new species and support separation at the rank of species of two varieties (G. suaveolens subsp. suaveolens var. gabonica, G. suaveolens subsp. suaveolens var. suaveolens) and one subspe
Keywords: African Research